A chiral covalent organic framework (COF) nanozyme with ultrahigh enzymatic activity. Issue 12 (2nd November 2020) - Zhou, Ya; Wei, Yue; Ren, Jinsong; Qu, Xiaogang
Abstract : The first chiral nanozyme with higher activity than the natural enzyme is designed based on mimicking the natural enzyme and covalent organic frameworks. Abstract : Herein, we report the first chiral nanozyme with higher activity than the natural enzyme, which is designed based on mimicking a natural enzyme and the superior structure of covalent organic framework (COF) materials. The well-dispersed iron porphyrin and l -histidine (l -His) units endow the COF nanozyme with high activity. The incorporation of l -His units also imbues the COF nanozyme with selectivity for l -dopa in the oxidation of dopa enantiomers with a selectivity factor up to 1.86, while replacing l -His with d -His can reverse the preference to d -dopa with a selectivity factor of 1.51. The activity and selectivity of the COF nanozyme can be optimized by varying the l -His content which can change the activation energy of the catalytic reactions and the substrate binding.